Hubungan Antar Faktor Penyebab Human Error Terhadap Jumlah Penyimpangan Produk Blister Di PT. XXX - Nurliya Irfiani; Aditya Trias Pradana; Agnes Nuniek Winantari (Fakultas Farmasi, Universitas Surabaya, 2018)
Human error is the main cause of blister product quality deviation at PT. XXX, which lead by personnel factor and work method. The research intends to analyze the relationship between personnel qualification level (blister production team), number of blister product and production length (Z blister machine), with blister product deviation at PT. XXX (2015-2017). The research was a descriptive-observational study (retrospective) by linier regression analysis using 2 variables and multi variable. The t-test analysis result between personnel qualification level and blister product deviation, p=0.041 (p<0.05) showed a significant relationship between those variables. The t-test analysis result between number of blister product and blister product deviation, p=0.164 (p>0.05) showed that there is no significant relationship between those variables. The result of t-test between production length (Z blister machine) and blister product deviation, p=0.542 (p>0.05) showed that there is no significant relationship between those variables. The F-test analysis result showed a significant relationship between personnel qualification level (blister production team), number of blister product and production length (Z blister machine) with blister product deviation (p=0,000; p<0.05).